2007
DOI: 10.1016/j.ejogrb.2006.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaginal delivery on endosonographic anal sphincter morphology

Abstract: Objective: To describe the effect of vaginal delivery with no clinically recognized sphincter tear on endosonographic anal sphincter morphology and sphincter pressure and to relate endosonographic results to anal sphincter pressure and anal incontinence score.Study design: Thirty-two nullipara underwent anal endosonography and anal manometry in the third trimester of pregnancy, 2 weeks and 6 months post-partum. The sphincter defect scores (1-16) and the thickness and length of the sphincters were measured by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
1
14
0
3
Order By: Relevance
“…Several studies showed that presence of a sphincter defect at EAUS does not automatically mean that the defect is the main culprit in the etiology of the patient's incontinence: 20 to 30 percent of women may have occult sphincter injuries after vaginal delivery, but only a portion of these women are symptomatic. 15,16 Consistent with this hypothesis, a prospective study looking at postnatal incontinence and presence of sphincter defects on EAUS in 159 women showed that a symptom questionnaire was inadequate to identify sphincter injuries after vaginal delivery. 17 The results of the study are interesting because they may raise a broader, interesting question as to whether external sphincter injuries, when present, are indeed the main cause of fecal incontinence.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies showed that presence of a sphincter defect at EAUS does not automatically mean that the defect is the main culprit in the etiology of the patient's incontinence: 20 to 30 percent of women may have occult sphincter injuries after vaginal delivery, but only a portion of these women are symptomatic. 15,16 Consistent with this hypothesis, a prospective study looking at postnatal incontinence and presence of sphincter defects on EAUS in 159 women showed that a symptom questionnaire was inadequate to identify sphincter injuries after vaginal delivery. 17 The results of the study are interesting because they may raise a broader, interesting question as to whether external sphincter injuries, when present, are indeed the main cause of fecal incontinence.…”
Section: Discussionmentioning
confidence: 89%
“…Wexner score is not necessarily related to the presence or absence of anal sphincter defects, because the score is affected by various factors such as stool hardness and restrictions of excretion behavior. However, anal sphincter defects caused by childbirth do not heal spontaneously [17,18]. Anal sphincter defects usually remain for a long period of time, and the symptoms of fecal incontinence get worse with age.…”
Section: Discussionmentioning
confidence: 99%
“…45% der Patientinnen und 38% der Probandinnen waren Nulliparae (U-Test nach Mann-Whitney: p > Aus ätiologischer Sicht liegen neben den eher seltenen kongenitalen, neurologischen und systemischen Formen der Inkontinenz ursächlich überwiegend geburtstraumatische Schädigungen des Kontinenzorgans zugrunde, gefolgt von iatrogenen Verletzungen infolge proktologischer Eingriffe [16,21]. Besonders häufig sind Multiparae, die Kinder mit einem Geburtsgewicht > 4 000 g geboren haben, welche vaginaloperativ mittels Vakuumextraktion oder Forceps entwickelt wurden, sowie Frauen, die ausgedehnte Geburtsverletzungen des Beckenbodens erlitten haben, betroffen [1,6,24]. Auch nach chirurgischen Interventionen wie z.B.…”
Section: Studien-und Kontrollkollektiveunclassified
“…Ebenso kann eine Schwangerschaft ursächlich für beide Krankheitsbilder verantwortlich gemacht werden. Durch muskuläre oder nervale Defekte des M. sphincter ani externus und des M. sphincter ani internus kommt es in 4-10% postpartal zu einer neu aufgetretenen Analinkontinenz [24,26]. Ab einem BMI > 30,0 kg/m 2 entsprechend einer Adipositas WHO-Gruppe I, in der auch bei der Analyse unseres Studienkollektivs ein signifikanter Zusammenhang mit dem Auftreten einer Stuhlinkontinenz nachgewiesen werden konnte, besteht ein hohes Risiko für Begleiterkrankungen des Überge-wichts [5,9].…”
Section: Diskussionunclassified